Functional Parathyroid Cyst: A Rare Cause of Malignant Hypercalcemia with Primary Hyperparathyroidism—A Case Report and Review of the Literature - Areej Khan; Yusra Khan; Shahzad Raza; Ghulam Akbar; Monis Khan; Nauman Diwan; Wajih Rizvi (Case Reports in Medicine)
Parathyroid cysts are rare lesions found in the neck and anterior mediastinum. They are often nonfunctional (>90%) and rarely in the functional form. This paper discusses a case of severe hypercalcemia (23 mg/dL) secondary to a rare functional parathyroid cyst. The patient was later found to have a hemorrhagic cyst with compression of the right recurrent laryngeal nerve. Preoperative diagnosis of the lesion was parathyroid carcinoma. However, reexploration of the parathyroid mass along with microscopic study confirmed the diagnosis of a parathyroid cyst. Following cystectomy, the patient restored her baseline functional status with preservation of the right recurrent laryngeal nerve. Postoperative followup three years later showed no evidence of cyst recurrence. This paper illustrates the rare presentation of parathyroid functional cysts with severe hypercalcemia and primary hyperparathyroidism. Physicians should be aware of the presence of hemorrhage, inflammation, and compressive symptoms in these cysts which mimic parathyroid carcinoma. These patients should be managed with aggressive medical and surgical intervention.